DOPO-HQ-based flame retardant, preparation method and application thereof, flame-retardant anti-dripping PET composite material and preparation of flame-retardant anti-dripping PET composite material

By using DOPO-HQ-based flame retardant to composite with PET, the problems of poor droplet resistance and large smoke release are solved, and the flame retardant and droplet resistance of PET composites are improved and the high-efficiency flame retardant effect is achieved.

CN119462765AActive Publication Date: 2025-02-18ZHEJIANG MEISHENG NEW MATERIALS CO LTD

Patent Information

Application Number
CN202411594338.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-09
Publication Date
2025-02-18
Estimated Expiration
2044-11-09

AI Technical Summary

Technical Problem

The existing PET materials have problems with poor droplet resistance and large smoke release, and when they are island components of island fibers, the flame retardant performance is insufficient.

Method used

Using DOPO-HQ-based flame retardant, a flame retardant with a high-efficiency phosphorus-based flame retardant DOPO structure and triazine structure was prepared by performing nucleophilic substitution reaction and condensation reaction in a protective atmosphere, and mixed it with PET in Grits were carried out in a twin-screw extruder to prepare flame retardant and drip-resistant PET composite material.

Benefits of technology

The flame retardant droplet resistance and anti-melting performance of PET composites has been improved, with high efficiency flame retardant self-extinguishing performance, low smoke release amount and no droplets. In the case of a small amount of added amount, the thermal performance is close to pure PET.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462765A_ABST
    Figure CN119462765A_ABST
Patent Text Reader

Abstract

The invention provides a DOPO-HQ-based flame retardant, a preparation method and application thereof, a flame-retardant anti-dripping PET composite material and preparation thereof, and belongs to the technical field of flame retardants. The DOPO-HQ-based flame retardant provided by the invention contains an efficient phosphorus-based flame retardant DOPO structure, so that the composite material can be endowed with efficient flame-retardant self-extinguishing performance; besides, the DOPO-HQ-based flame retardant contains a triazine structure, is high in thermal stability and has excellent high-temperature carbonization capacity, so that a large number of carbon layers are generated in the combustion process of the composite material and cover the surface of a base material, and the effects of molten drop resistance and smoke suppression are achieved. The thermal performance of the flame-retardant PET composite material prepared from the DOPO-HQ-based flame retardant is similar to that of pure PET, and the flame-retardant PET composite material has the characteristics of high flame-retardant efficiency, no halogen, no molten drop, low smoke release amount and the like under the condition of a small addition amount (2-8wt%) (the current commercially available flame-retardant anti-molten drop addition amount is greater than or equal to 15wt%).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of flame retardants, and in particular to a DOPO-HQ-based flame retardant and a preparation method and application thereof, and a flame-retardant and anti-melting droplet PET composite material and a preparation thereof. Background Art

[0002] Sea-island fiber is a composite fiber developed in the early 1970s. It has the characteristics of high added value and high performance. Polyethylene terephthalate (PET) is a common island component in sea-island fiber. The developed sea-island fiber has many excellent properties, such as smoothness, good adsorption performance, soft and elegant luster, etc. PET has good heat resistance, chemical stability, mechanical properties and excellent spinnability, and is widely used in the fields of film, packaging materials and textile decorative materials. However, PET is very easy to burn, with a limiting oxygen index of only 21%, which is a flammable material; and a large number of flaming droplets will be produced during its combustion, which will not only cause burns and scalds to people, but also cause the flame to spread rapidly and even cause secondary fires. However, the current mainstream commercial flame retardants are mainly single phosphorus-based, and phosphorus-based flame retardants mainly achieve flame retardancy by promoting melt dripping during PET combustion; anti-drip agents often do not have flame retardant properties, and a large amount of addition is required to give PET real anti-drip properties, making the compatibility of PET composite materials poor. Therefore, how to simultaneously achieve flame retardant modification and anti-drip modification of PET has gradually become a research hotspot and main research direction for many experts and scholars.

[0003] 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO-HQ) is a commercial phosphorus-based flame retardant with high flame retardant efficiency. At present, domestic and foreign scholars have used the flame retardant DOPO-HQ for flame retardant modification of fiber-reinforced polybutylene terephthalate (LGF / PBT), epoxy resin and other polymers. Sun et al. (Sun J, Zhang D, Shang X, et al. Flame-retardant properties and mechanism of LGF / PBT / DOPO-HQ-conjugated flame-retardant composites[J]. Frontiers in Chemistry, 2022, 10: 981579.) used DOPO-HQ to modify LGF / PBT. When its content reached 14wt%, the LGF / PBT / DOPO-HQ composite material reached UL 94V-0 grade (no droplets), and the LOI value increased from 21.2 to 26.4%. Wang et al. (Wang W, Cao Z, Wang Z. Investigation on the flame retardancy, thermal and mechanical properties of epoxy resin / cyanate ester composites based on mSiO2@ZrPB and DOPO-HQ[J]. Polymers for Advanced Technologies, 2023, 34(5): 1540-1556.) mixed mesoporous silica and N,N′-piperazine (dimethylenephosphonic acid zirconium) (mSiO2@ZrPB) with DOPO-HQ in a certain proportion and used it to cure epoxy resin / cyanate ester (EPC E) copolymers. The study found that the EPCE composite containing 8.0wt% DOPO-HQ and 2.0wt% mSiO2@Zr PB reached UL-94V-0 and the limiting oxygen index was as high as 30.5%.

[0004] However, existing PET materials still have problems such as poor anti-melting droplet resistance and large smoke release, and there are few studies on its flame retardant properties when used as the island component of sea-island fibers. Therefore, based on the current research status of DO PO-HQ-based flame retardants and PET, it is of great significance to carry out innovative design of DOPO-HQ-based flame retardants, improve the flame retardant properties of PET composites, and achieve high-quality preparation of sea-island fibers, which needs to be solved urgently. Summary of the invention

[0005] The purpose of the present invention is to provide a DOPO-HQ-based flame retardant and a preparation method and application thereof, a flame-retardant and anti-melting drip PET composite material and its preparation, so as to solve the problems of poor anti-melting dripping property and large smoke release of existing PET materials, realize the flame retardancy and anti-melting dripping of PET, and improve the flame retardant performance when used as the island component of sea-island fibers.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a DOPO-HQ-based flame retardant having a structure described in Formula 1:

[0008]

[0009] In formula I, 5≤n≤10;

[0010] R includes

[0011] The present invention provides a method for preparing the DOPO-HQ-based flame retardant described in the above technical solution, comprising the following steps:

[0012] In a protective atmosphere, cyanuric chloride, an aromatic compound, a first catalyst and a first organic solvent are mixed to perform a nucleophilic substitution reaction to obtain an intermediate product;

[0013] The intermediate product, DOPO-HQ, a second catalyst and a second organic solvent are mixed to carry out a condensation reaction to obtain a DOPO-HQ-based flame retardant;

[0014] The aromatic compound includes p-methylphenol, biphenyl alcohol, 3-phenylvinylphenol, 2-hydroxybenzimidazole or p-hydroxybenzonitrile.

[0015] Preferably, the first catalyst comprises pyridine, triethylamine, sodium acetate or anhydrous potassium carbonate; and the mass ratio of the cyanuric chloride, the aromatic compound and the first catalyst is 1-2.5:0.8-2.5:1.

[0016] Preferably, the first organic solvent includes ethanol, dichloromethane, chloroform or acetone; the temperature of the nucleophilic substitution reaction is 40-60° C., and the time is 2-4 hours.

[0017] Preferably, the second catalyst comprises pyridine, triethylamine, sodium acetate or N,N-diisopropylethylamine; the mass ratio of the intermediate product to DOPO-HQ is 1:1-1.8; the mass ratio of the intermediate product to the second catalyst is 1:0.5-1.4.

[0018] Preferably, the second organic solvent includes dimethyl sulfoxide, tetrahydrofuran, N,N-dimethylformamide or acetone; the temperature of the condensation reaction is 80-120° C., and the time is 10-12 hours.

[0019] The present invention provides the use of the DOPO-HQ-based flame retardant described in the above technical solution or the DOPO-HQ-based flame retardant prepared by the preparation method described in the above technical solution in the preparation of a flame-retardant and anti-drip PET composite material.

[0020] The present invention provides a flame-retardant and anti-melting droplet PET composite material, comprising the following raw materials in parts by weight: 100 parts of PET, 2 to 8 parts of DOPO-HQ-based flame retardant;

[0021] The DOPO-HQ-based flame retardant is the DOPO-HQ-based flame retardant described in the above technical solution or the DOPO-HQ-based flame retardant prepared by the preparation method described in the above technical solution.

[0022] The present invention provides a method for preparing the flame-retardant and anti-drip PET composite material described in the above technical solution, comprising the following steps:

[0023] PET and DOPO-HQ-based flame retardant are mixed and granulated in a twin-screw extruder to obtain a DOPO-HQ-based flame retardant PET composite material.

[0024] Preferably, the temperature of the extruder is set as follows: zone 1 temperature: 255-265°C; zone 2 temperature 255-265°C; zone 3 temperature 265-275°C; zone 4 temperature 265-275°C; zone 5 temperature 265-275°C.

[0025] The present invention provides a DOPO-HQ-based flame retardant, which contains a high-efficiency phosphorus-based flame retardant DOPO structure and can give a composite material a high-efficiency flame retardant and self-extinguishing performance; in addition, the DOPO-HQ-based flame retardant contains a triazine structure, has high thermal stability and excellent high-temperature carbonization ability, so that the composite material produces a large amount of carbon layer during the combustion process and covers the surface of the substrate, thereby achieving the effect of anti-dripping and smoke suppression.

[0026] The thermal properties of the flame-retardant PET composite material prepared by using the DOPO-HQ-based flame retardant are similar to those of pure PET. When added in a small amount (2 to 8 wt%) (the current commercially available flame retardant and anti-melting droplet addition amount is ≥15 wt%), it has the characteristics of high flame retardant efficiency, halogen-free, no melting droplets, and low smoke release. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The synthetic route of DOPO-HQ-based flame retardant I in Examples 1 to 2;

[0028] Figure 2The synthetic route of DOPO-HQ-based flame retardant II in Examples 3 to 4;

[0029] Figure 3 The synthetic route of DOPO-HQ-based flame retardant III in Examples 5 to 6;

[0030] Figure 4 The synthetic route of DOPO-HQ-based flame retardant IV in Examples 7 to 8;

[0031] Figure 5 is a synthetic route diagram of the DOPO-HQ-based flame retardant V in Examples 9 to 10;

[0032] Figure 6 This is the infrared spectrum of flame retardant V prepared in Example 9. DETAILED DESCRIPTION

[0033] In the present invention, unless otherwise specified, the required raw materials or reagents are commercially available products well known to those skilled in the art.

[0034] The present invention provides a DOPO-HQ-based flame retardant having a structure described in Formula 1:

[0035]

[0036] In formula I, 5≤n≤10;

[0037] R includes

[0038] The DOPO-HQ-based flame retardant of the present invention is preferably

[0039]

[0040] The present invention provides a method for preparing the DOPO-HQ-based flame retardant described in the above technical solution, comprising the following steps:

[0041] In a protective atmosphere, cyanuric chloride, an aromatic compound, a first catalyst and a first organic solvent are mixed to perform a nucleophilic substitution reaction to obtain an intermediate product;

[0042] The intermediate product, DOPO-HQ, a second catalyst and a second organic solvent are mixed to carry out a condensation reaction to obtain a DOPO-HQ-based flame retardant;

[0043] The aromatic compound includes p-methylphenol, biphenyl alcohol, 3-phenylvinylphenol, 2-hydroxybenzimidazole or p-hydroxybenzonitrile.

[0044] The present invention mixes cyanuric chloride, aromatic compounds, a first catalyst and a first organic solvent in a protective atmosphere to carry out a nucleophilic substitution reaction to obtain an intermediate product.

[0045] In the present invention, the protective atmosphere preferably comprises nitrogen;

[0046] The first catalyst preferably includes pyridine, triethylamine, sodium acetate or anhydrous potassium carbonate; the mass ratio of the cyanuric chloride, the aromatic compound and the first catalyst is preferably 1-2.5:0.8-2.5:1.

[0047] In the present invention, the first organic solvent includes ethanol, dichloromethane, chloroform or acetone; the present invention has no special limitation on the amount of the first organic solvent, which can be adjusted according to actual needs to ensure smooth reaction.

[0048] In the present invention, cyanuric chloride and an aromatic compound are preferably mixed, stirred to fully dissolve the reactants in the first organic solvent, and then the first catalyst is added to react under stirring conditions. The present invention has no particular limitation on the stirring, and the stirring can be carried out according to a process well known in the art.

[0049] In the present invention, the temperature of the nucleophilic substitution reaction is preferably 40-60° C., more preferably 50° C., and the time is preferably 2-4 h, more preferably 3 h.

[0050] After the nucleophilic substitution reaction is completed, the present invention preferably filters and washes the obtained product in sequence, and dries the obtained solid at 60-80° C. for 6-8 hours to obtain an intermediate product; the washing is preferably carried out in sequence with deionized water and tetrahydrofuran for 3-6 times each. The present invention has no special limitation on the filtration, and it can be carried out according to the process well known in the art.

[0051] After obtaining the intermediate product, the present invention mixes the intermediate product, DOPO-HQ, a second catalyst and a second organic solvent to carry out a condensation reaction to obtain a DOPO-HQ-based flame retardant.

[0052] In the present invention, the DOPO-HQ (10-(2,5-dihydroxyphenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide) has a CAS number of 99208-50-1 and is a commercially available product.

[0053] In the present invention, the second catalyst preferably includes pyridine, triethylamine, sodium acetate or N,N-diisopropylethylamine (DIEA); the mass ratio of the intermediate product to DOPO-HQ is preferably 1:1-1.8, more preferably 1:1.2-1.3; the mass ratio of the intermediate product to the second catalyst is preferably 1:0.5-1.4, more preferably 1:1.2-1.3.

[0054] In the present invention, the second organic solvent preferably includes dimethyl sulfoxide, tetrahydrofuran, N,N-dimethylformamide or acetone; the present invention has no special limitation on the amount of the second organic solvent, which can be adjusted according to actual needs to ensure smooth reaction.

[0055] In the present invention, the intermediate product, DOPO-HQ and the second catalyst are preferably added to an organic solvent under a protective atmosphere to carry out a condensation reaction; the protective atmosphere preferably includes nitrogen.

[0056] In the present invention, the temperature of the condensation reaction is preferably 80 to 120° C., more preferably 90 to 100° C., and the time is preferably 10 to 12 hours.

[0057] After the condensation reaction is completed, the present invention preferably filters and washes the obtained product in sequence, and dries the obtained solid at 60-80° C. for 6-8 hours to obtain a DOPO-HQ-based flame retardant; the washing is preferably performed by washing with deionized water and acetone 3-6 times in sequence.

[0058] The present invention provides the use of the DOPO-HQ-based flame retardant described in the above technical solution or the DOPO-HQ-based flame retardant prepared by the preparation method described in the above technical solution in the preparation of a flame-retardant and anti-drip PET composite material.

[0059] The present invention provides a flame-retardant and anti-melting droplet PET composite material, comprising the following raw materials in parts by weight: 100 parts of PET, 2 to 8 parts of DOPO-HQ-based flame retardant;

[0060] The DOPO-HQ-based flame retardant is the DOPO-HQ-based flame retardant described in the above technical solution or the DOPO-HQ-based flame retardant prepared by the preparation method described in the above technical solution.

[0061] The present invention has no particular limitation on the specifications of the PET, and any commercially available product known in the art may be used.

[0062] In the present invention, the amount of the DOPO-HQ-based flame retardant is preferably 3 to 6 parts, more preferably 4 to 5 parts.

[0063] The present invention provides a method for preparing the flame-retardant and anti-drip PET composite material described in the above technical solution, comprising the following steps:

[0064] PET and DOPO-HQ-based flame retardant are mixed and granulated in a twin-screw extruder to obtain a DOPO-HQ-based flame retardant PET composite material.

[0065] In the present invention, the temperature setting of the extruder is preferably: zone one temperature: 255-265°C; zone two temperature 255-265°C; zone three temperature 265-275°C; zone four temperature 265-275°C; zone five temperature 265-275°C; zone one temperature is more preferably 260°C, zone two temperature is more preferably 260°C; zone three temperature is more preferably 270°C; zone four temperature is more preferably 270°C; zone five temperature is more preferably 270°C.

[0066] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0067] In the following examples, PET slices were purchased from China Resources Chemical Materials Co., Ltd., CR-8863.

[0068] Example 1

[0069] Preparation of DOPO-HQ-based flame retardant Ⅰ Figure 1 As shown:

[0070] Step 1: Under nitrogen protection, add 37 g of cyanuric chloride and 22 g of p-methylphenol into a three-necked round-bottom flask, stir to dissolve the reactants in ethanol, add 16 g of pyridine into the flask, control the temperature at 60° C. and stir for 4 h to obtain a reaction mixture;

[0071] Step 2: After the reaction in step 1 is completed, the solid is filtered, washed three times with deionized water and tetrahydrofuran, and dried at 80° C. for 6 hours to obtain an intermediate product;

[0072] Step 3: After step 2 is completed, under nitrogen protection, 52 g of the intermediate product, 65 g of DOPO-HQ, and 30 g of triethylamine are added to a three-necked flask filled with dimethyl sulfoxide, and a condensation reaction is carried out at a temperature of 80° C. for 10 hours to obtain a reaction mixture;

[0073] Step 4: After the reaction in step 3 is completed, the mixture is filtered, washed three times with deionized water and acetone respectively, and the obtained solid is dried at 60° C. for 6 h to obtain a DOPO-HQ-based flame retardant (n=6);

[0074] Preparation of DOPO-HQ-based flame-retardant PET composite material Ⅰ-I:

[0075] By weight, 100 parts of PET chips and 6 parts of prepared DOPO-HQ-based flame retardant I were added to a twin-screw extruder, and the temperature was set as follows: zone 1 temperature: 255°C; zone 2 temperature 255°C; zone 3 temperature 265°C; zone 4 temperature 265°C; zone 5 temperature 265°C to obtain DOPO-HQ-based flame-retardant PET composite material II.

[0076] Performance Testing

[0077] The performance of the prepared PET composite material II was tested by vertical combustion test and limiting oxygen index method, and compared with pure PET (PET slice) (vertical combustion test NR, peak smoke release rate 0.1113m 2 / s, the total smoke release is 17.7m 2 ) comparison, the results show that the prepared DOPO-HQ-based flame retardant PET composite material II is resistant to dripping, and the vertical burning test is V-0 level, the peak smoke release rate and total smoke release are reduced by 30.1% and 23.2% respectively compared with PET chips.

[0078] Example 2

[0079] Preparation of DOPO-HQ-based flame retardant Ⅰ Figure 1 As shown:

[0080] Step 1: Under nitrogen protection, add 37 g of cyanuric chloride and 22 g of p-methylphenol into a three-necked round-bottom flask, stir to dissolve the reactants in dichloromethane, then add 20 g of triethylamine into the flask, control the temperature at 60° C. and stir for 4 h to obtain a reaction mixture;

[0081] Step 2: After the reaction in step 1 is completed, the solid is filtered, washed three times with deionized water and tetrahydrofuran, and dried at 80° C. for 6 hours to obtain an intermediate product;

[0082] Step 3: After step 2 is completed, under nitrogen protection, 52 g of the intermediate product, 78 g of DOPO-HQ, and 31 g of DIEA are added to a three-necked flask filled with dimethyl sulfoxide, and a condensation reaction is carried out at a temperature of 80° C. for 12 hours to obtain a reaction mixture;

[0083] Step 4: After the reaction in step 3 is completed, the mixture is filtered, washed three times with deionized water and acetone, and the obtained solid is dried at 60° C. for 6 h to obtain a DOPO-HQ-based flame retardant (n=8);

[0084] Preparation of DOPO-HQ-based flame-retardant PET composite materials Ⅰ-Ⅱ:

[0085] By weight, 100 parts of PET chips and 4 parts of prepared DOPO-HQ-based flame retardant I were added to a twin-screw extruder, and the temperature was set as follows: zone 1 temperature: 255°C; zone 2 temperature 255°C; zone 3 temperature 265°C; zone 4 temperature 265°C; zone 5 temperature 265°C to obtain DOPO-HQ-based flame-retardant PET composite materials I-Ⅱ.

[0086] Performance Testing

[0087] The performance of the prepared PET composite materials I-Ⅱ was tested by vertical burning test and limiting oxygen index method and compared with pure PET. The results showed that the prepared DOPO-HQ-based flame retardant PET composite materials I-Ⅱ were resistant to dripping, and the vertical burning test was V-1 level. The peak smoke release rate and total smoke release were reduced by 28.8% and 20.5% respectively compared with PET slices.

[0088] Example 3

[0089] Preparation of DOPO-HQ-based flame retardant II Figure 2 As shown:

[0090] Step 1: Under nitrogen protection, add 37 g of cyanuric chloride and 40 g of 2-biphenyl alcohol into a three-necked round-bottom flask, stir to dissolve the reactants in ethanol, then add 16 g of sodium acetate into the flask, control the temperature at 50° C. and stir for 3 h to obtain a reaction mixture;

[0091] Step 2: After the reaction in step 1 is completed, the solid is filtered, washed three times with deionized water and tetrahydrofuran, and dried at 60° C. for 8 h to obtain an intermediate product;

[0092] Step 3: After step 2 is completed, under nitrogen protection, 70 g of the intermediate product, 78 g of DOPO-HQ, and 70 g of sodium acetate are added to a three-necked flask filled with tetrahydrofuran, and condensation reaction is carried out at a temperature of 100° C. for 12 hours to obtain a reaction mixture;

[0093] Step 4: After the reaction in step 3 is completed, the mixture is filtered, washed three times with deionized water and acetone respectively, and the obtained solid is dried at 60° C. for 8 h to obtain a DOPO-HQ-based flame retardant (n=5);

[0094] Preparation of DOPO-HQ-based flame-retardant PET composite materials Ⅱ-Ⅰ:

[0095] By weight, 100 parts of PET chips and 6 parts of prepared DOPO-HQ-based flame retardant II were added to a twin-screw extruder, and the temperature was set as follows: zone 1 temperature: 255°C; zone 2 temperature 255°C; zone 3 temperature 265°C; zone 4 temperature 265°C; zone 5 temperature 265°C to obtain DOPO-HQ-based flame-retardant PET composite material II-I.

[0096] Performance Testing

[0097] The performance of the prepared PET composite material was tested by vertical burning test and limiting oxygen index method and compared with pure PET. The results showed that the prepared DOPO-HQ-based flame retardant PET composite material Ⅱ-I was resistant to dripping, and the vertical burning test was V-0 level. The peak smoke release rate and total smoke release were reduced by 31.6% and 23.7% respectively compared with PET slices.

[0098] Example 4

[0099] Preparation of DOPO-HQ-based flame retardant II Figure 2 As shown:

[0100] Step 1: Under nitrogen protection, add 37 g of cyanuric chloride and 40 g of 2-biphenyl alcohol into a three-necked round-bottom flask, stir to dissolve the reactants in chloroform, then add 28 g of anhydrous potassium carbonate into the flask, control the temperature at 50° C. and stir for 3 h to obtain a reaction mixture;

[0101] Step 2: After the reaction in step 1 is completed, the solid is filtered, washed three times with deionized water and tetrahydrofuran, and dried at 60° C. for 8 h to obtain an intermediate product;

[0102] Step 3: After step 2 is completed, under nitrogen protection, 70 g of the intermediate product, 85 g of DOPO-HQ, and 80 g of pyridine are added to a three-necked flask filled with tetrahydrofuran, and a condensation reaction is carried out at a temperature of 120° C. for 12 hours to obtain a reaction mixture;

[0103] Step 4: After the reaction in step 3 is completed, the mixture is filtered, washed three times with deionized water and acetone respectively, and the obtained solid is dried at 60° C. for 8 h to obtain a DOPO-HQ-based flame retardant (n=6);

[0104] Preparation of DOPO-HQ-based flame-retardant PET composite material Ⅱ-Ⅱ:

[0105] By weight, 100 parts of PET chips and 4 parts of prepared DOPO-HQ-based flame retardant II were added to a twin-screw extruder, and the temperature was set as follows: zone 1 temperature: 255°C; zone 2 temperature 255°C; zone 3 temperature 265°C; zone 4 temperature 265°C; zone 5 temperature 265°C to obtain DOPO-HQ-based flame-retardant PET composite material II-II.

[0106] Performance Testing

[0107] The performance of the prepared PET composite material was tested by vertical burning test and limiting oxygen index method and compared with pure PET. The results showed that the prepared DOPO-HQ-based flame retardant PET composite material Ⅱ-Ⅱ was resistant to dripping, and the vertical burning test was V-1 level. The peak smoke release rate and total smoke release were reduced by 29.2% and 21.7% respectively compared with PET slices.

[0108] Example 5

[0109] Preparation of DOPO-HQ-based flame retardant III Figure 3 As shown:

[0110] Step 1: Under nitrogen protection, 37 g of cyanuric chloride and 40 g of 3-phenylvinylphenol were added to a three-necked round-bottom flask, and the reactants were dissolved in ethanol by stirring. Then, 20 g of triethylamine was added to the flask, and the temperature was controlled at 40° C. and stirred for 4 h to obtain a reaction mixture;

[0111] Step 2: After the reaction in step 1 is completed, the solid is filtered, washed three times with deionized water and tetrahydrofuran, and dried at 60° C. for 8 h to obtain an intermediate product;

[0112] Step 3: After step 2 is completed, under nitrogen protection, 70 g of the intermediate product, 91 g of DOPO-HQ, and 36 g of DIEA are added to a three-necked flask filled with tetrahydrofuran, and a condensation reaction is carried out at a temperature of 90° C. for 10 hours to obtain a reaction mixture;

[0113] Step 4: After the reaction in step 3 is completed, the mixture is filtered, washed three times with deionized water and acetone, and the obtained solid is dried at 60° C. for 6 h to obtain a DOPO-HQ-based flame retardant (n=7);

[0114] Preparation of DOPO-HQ-based flame-retardant PET composite materials III-I:

[0115] By weight, 100 parts of PET chips and 6 parts of prepared DOPO-HQ-based flame retardant III were added to a twin-screw extruder, and the temperature was set as follows: zone 1 temperature: 260°C; zone 2 temperature 260°C; zone 3 temperature 270°C; zone 4 temperature 270°C; zone 5 temperature 270°C to obtain DOPO-HQ-based flame-retardant PET composite material III-I.

[0116] Performance Testing

[0117] The performance of the prepared PET composite material was tested by vertical burning test and limiting oxygen index method and compared with pure PET. The results showed that the prepared DOPO-HQ-based flame retardant PET composite material III-I was resistant to dripping, and the vertical burning test was V-0 level. The peak smoke release rate and total smoke release were reduced by 32.3% and 24.9% respectively compared with PET slices.

[0118] Example 6

[0119] Preparation of DOPO-HQ-based flame retardant III Figure 3 As shown:

[0120] Step 1: Under nitrogen protection, 37 g of cyanuric chloride and 40 g of 3-phenylvinylphenol were added to a three-necked round-bottom flask, and the reactants were dissolved in dichloromethane by stirring. Then, 16 g of sodium acetate was added to the flask, and the temperature was controlled at 40° C. and stirred for 4 h to obtain a reaction mixture;

[0121] Step 2: After the reaction in step 1 is completed, the solid is filtered, washed three times with deionized water and tetrahydrofuran, and dried at 60° C. for 8 h to obtain an intermediate product;

[0122] Step 3: After step 2 is completed, under nitrogen protection, 70 g of the intermediate product, 72 g of DOPO-HQ, and 50 g of pyridine are added to a three-necked flask filled with dimethyl sulfoxide, and a condensation reaction is carried out at a temperature of 100° C. for 12 hours to obtain a reaction mixture;

[0123] Step 4: After the reaction in step 3 is completed, the mixture is filtered, washed three times with deionized water and acetone, and the obtained solid is dried at 80° C. for 6 h to obtain a DOPO-HQ-based flame retardant (n=8);

[0124] Preparation of DOPO-HQ-based flame-retardant PET composite materials III-II:

[0125] By weight, 100 parts of PET chips and 8 parts of prepared DOPO-HQ-based flame retardant III were added to a twin-screw extruder, and the temperature was set as follows: zone 1 temperature: 260°C; zone 2 temperature 260°C; zone 3 temperature 270°C; zone 4 temperature 270°C; zone 5 temperature 270°C to obtain DOPO-HQ-based flame-retardant PET composite materials III-II.

[0126] Performance Testing

[0127] The performance of the prepared PET composite material was tested by vertical burning test and limiting oxygen index method and compared with pure PET. The results showed that the prepared DOPO-HQ-based flame retardant PET composite material III-II was resistant to dripping, and the vertical burning test was V-0 level. The peak smoke release rate and total smoke release were reduced by 33.6% and 25.7% respectively compared with PET slices.

[0128] Example 7

[0129] Preparation of DOPO-HQ-based flame retardant IV Figure 4 As shown:

[0130] Step 1: Under nitrogen protection, 37 g of cyanuric chloride and 27 g of 2-hydroxybenzimidazole were added to a three-necked round-bottom flask, and the reactants were dissolved in acetone by stirring. Then, 20 g of triethylamine was added to the flask, and the temperature was controlled at 60° C. and stirred for 4 h to obtain a reaction mixture;

[0131] Step 2: After the reaction in step 1 is completed, the solid is filtered, washed three times with deionized water and tetrahydrofuran, and dried at 80° C. for 6 hours to obtain an intermediate product;

[0132] Step 3: After step 2 is completed, under nitrogen protection, 56 g of the intermediate product, 78 g of DOPO-HQ, and 28 g of pyridine are added to a three-necked flask filled with N,N-dimethylformamide, and a condensation reaction is carried out at a temperature of 80° C. for 10 hours to obtain a reaction mixture;

[0133] Step 4: After the reaction in step 3 is completed, the mixture is filtered, washed three times with deionized water and acetone, and the obtained solid is dried at 60° C. for 6 h to obtain a DOPO-HQ-based flame retardant (n=9);

[0134] Preparation of DOPO-HQ-based flame-retardant PET composite material IV-I:

[0135] By weight, 100 parts of PET chips and 6 parts of prepared DOPO-HQ-based flame retardant IV were added to a twin-screw extruder, and the temperature was set as follows: zone 1 temperature: 260°C; zone 2 temperature 260°C; zone 3 temperature 270°C; zone 4 temperature 270°C; zone 5 temperature 270°C to obtain DOPO-HQ-based flame-retardant PET composite material IV-I.

[0136] Performance Testing

[0137] The performance of the prepared PET composite material was tested by vertical burning test and limiting oxygen index method and compared with pure PET. The results showed that the prepared DOPO-HQ-based flame retardant PET composite material IV-I was resistant to dripping, and the vertical burning test was V-0 level. The peak smoke release rate and total smoke release were reduced by 33.1% and 25.3% respectively compared with PET slices.

[0138] Example 8

[0139] Preparation of DOPO-HQ-based flame retardant IV Figure 4 As shown:

[0140] Step 1: Under nitrogen protection, 37 g of cyanuric chloride and 27 g of 2-hydroxybenzimidazole were added to a three-necked round-bottom flask, and the reactants were dissolved in acetone by stirring. Then, 20 g of triethylamine was added to the flask, and the temperature was controlled at 60° C. and stirred for 4 h to obtain a reaction mixture;

[0141] Step 2: After the reaction in step 1 is completed, the solid is filtered, washed three times with deionized water and tetrahydrofuran, and dried at 80° C. for 6 hours to obtain an intermediate product;

[0142] Step 3: After step 2 is completed, under nitrogen protection, 56 g of the intermediate product, 91 g of DOPO-HQ, and 30 g of sodium acetate are added to a three-necked flask filled with N,N-dimethylformamide, and a condensation reaction is carried out at a temperature of 80° C. for 10 hours to obtain a reaction mixture;

[0143] Step 4: After the reaction in step 3 is completed, the mixture is filtered, washed three times with deionized water and acetone respectively, and the obtained solid is dried at 60° C. for 6 hours to obtain a DOPO-HQ-based flame retardant;

[0144] Preparation of DOPO-HQ-based flame-retardant PET composite material IV-I:

[0145] By weight, 100 parts of PET chips and 4 parts of prepared DOPO-HQ-based flame retardant IV were added to a twin-screw extruder, and the temperature was set as follows: zone 1 temperature: 260°C; zone 2 temperature 260°C; zone 3 temperature 270°C; zone 4 temperature 270°C; zone 5 temperature 270°C to obtain DOPO-HQ-based flame-retardant PET composite material IV-I.

[0146] Performance Testing

[0147] The performance of the prepared PET composite material was tested by vertical burning test and limiting oxygen index method and compared with pure PET. The results showed that the prepared DOPO-HQ-based flame retardant PET composite material IV-II was resistant to dripping, and the vertical burning test was V-0 level. The peak smoke release rate and total smoke release were reduced by 32.0% and 24.4% respectively compared with PET slices.

[0148] Example 9

[0149] Preparation of DOPO-HQ-based flame retardant V Figure 5 As shown:

[0150] Step 1: Under nitrogen protection, add 37 g of cyanuric chloride and 24 g of p-hydroxybenzonitrile into a three-necked round-bottom flask, stir to dissolve the reactants in chloroform, then add 28 g of anhydrous potassium carbonate into the flask, control the temperature at 50°C and stir for 2 h to obtain a reaction mixture;

[0151] Step 2: After the reaction in step 1 is completed, the solid is filtered, washed three times with deionized water and tetrahydrofuran, and dried at 60° C. for 8 h to obtain an intermediate product;

[0152] Step 3: After step 2 is completed, under nitrogen protection, 54 g of the intermediate product, 66 g of DOPO-HQ, and 28 g of triethylamine are added to a three-necked flask filled with acetone, and a condensation reaction is carried out at a temperature of 120° C. for 10 hours to obtain a reaction mixture;

[0153] Step 4: After the reaction in step 3 is completed, the mixture is filtered, washed three times with deionized water and acetone, and the obtained solid is dried at 80° C. for 6 h to obtain a DOPO-HQ-based flame retardant (n=6);

[0154] Preparation of DOPO-HQ-based flame-retardant PET composite material V-Ⅰ:

[0155] By weight, 100 parts of PET chips and 4 parts of prepared DOPO-HQ-based flame retardant V were added to a twin-screw extruder, and the temperature was set as follows: zone 1 temperature: 265°C; zone 2 temperature 265°C; zone 3 temperature 275°C; zone 4 temperature 275°C; zone 5 temperature 275°C to obtain DOPO-HQ-based flame-retardant PET composite material V-I.

[0156] Performance Testing

[0157] The performance of the prepared PET composite material was tested by vertical burning test and limiting oxygen index method and compared with pure PET. The results showed that the prepared DOPO-HQ-based flame retardant PET composite material was V-Ⅰ resistant to dripping, and the vertical burning test was V-0 level. The peak smoke release rate and total smoke release were reduced by 33.3% and 25.8% respectively compared with PET slices.

[0158] Figure 6 The infrared spectrum of the flame retardant V prepared in Example 9; Figure 6 As shown, flame retardant V has a wavelength of 2231 cm -1 、1500cm -1 、943cm -1 The absorption peaks at correspond to -CN, triazine ring and DOPO-HQ structure, respectively, confirming that flame retardant V has been successfully prepared.

[0159] Example 10

[0160] Preparation of DOPO-HQ-based flame retardant V Figure 5 As shown:

[0161] Step 1: Under nitrogen protection, add 37 g of cyanuric chloride and 24 g of p-hydroxybenzonitrile into a three-necked round-bottom flask, stir to dissolve the reactants in chloroform, then add 28 g of anhydrous potassium carbonate into the flask, control the temperature at 60° C. and stir for 4 h to obtain a reaction mixture;

[0162] Step 2: After the reaction in step 1 is completed, the solid is filtered, washed three times with deionized water and tetrahydrofuran, and dried at 60° C. for 8 h to obtain an intermediate product;

[0163] Step 3: After step 2 is completed, under nitrogen protection, 55 g of the intermediate product, 65 g of DOPO-HQ, and 35 g of triethylamine are added to a three-necked flask filled with acetone, and a condensation reaction is carried out at a temperature of 120° C. for 10 hours to obtain a reaction mixture;

[0164] Step 4: After the reaction in step 3 is completed, the mixture is filtered, washed three times with deionized water and acetone, and the obtained solid is dried at 80° C. for 6 h to obtain a DOPO-HQ-based flame retardant (n=5);

[0165] Preparation of DOPO-HQ-based flame-retardant PET composite material V-Ⅰ:

[0166] By weight, 100 parts of PET chips and 2 parts of prepared DOPO-HQ-based flame retardant V were added to a twin-screw extruder, and the temperature was set as follows: zone 1 temperature: 265°C; zone 2 temperature 265°C; zone 3 temperature 275°C; zone 4 temperature 275°C; zone 5 temperature 275°C to obtain DOPO-HQ-based flame-retardant PET composite material V-Ⅱ.

[0167] Performance Testing

[0168] The performance of the prepared PET composite material was tested by vertical burning test and limiting oxygen index method and compared with pure PET. The results showed that the prepared DOPO-HQ-based flame retardant PET composite material was V-Ⅱ anti-dripping, and the vertical burning test was V-0 level. The peak smoke release rate and total smoke release were reduced by 32.2% and 25.0% respectively compared with PET slices.

[0169] Comparative Example 1

[0170] Preparation of DOPO-HQ flame retardant PET composites:

[0171] By weight, 100 parts of PET chips and 8 parts of flame retardant DOPO-HQ (Zhengzhou Yande Biotechnology Co., Ltd.) were added to a twin-screw extruder, and the temperature was set as follows: zone 1 temperature: 255°C; zone 2 temperature: 255°C; zone 3 temperature: 255°C; zone 4 temperature: 255°C; zone 5 temperature: 255°C to obtain a composite material of DOPO-HQ and PET.

[0172] Performance Testing

[0173] The performance of the prepared PET composite material was tested by vertical burning test and limiting oxygen index method and compared with pure PET. The results showed that there was a molten droplet phenomenon in the combustion process of the prepared DOPO-HQ-based flame-retardant PET composite material, and the vertical burning test was V-1 level. The peak smoke release rate and total smoke release increased by 25.2% and 15.0% respectively compared with PET slices.

[0174] Comparative Example 2

[0175] Preparation of triazine-based flame-retardant PET composites:

[0176] By weight, 100 parts of PET chips and 15 parts of the intermediate product (triazine-based flame retardant) prepared in step 2 of Example 9 were added to a twin-screw extruder, and the temperature was set as follows: zone 1 temperature: 260°C; zone 2 temperature: 260°C; zone 3 temperature: 270°C; zone 4 temperature: 270°C; zone 5 temperature: 270°C to obtain a composite material of triazine-based flame retardant and PET.

[0177] Performance Testing

[0178] The performance of the prepared PET composite material was tested by vertical combustion test and limiting oxygen index method and compared with pure PET. The results showed that the triazine-based flame-retardant PET composite material had droplet phenomenon during combustion, the vertical combustion test was V-2 level, and the peak smoke release rate and total smoke release were reduced by 10.2% and 6.0% respectively compared with PET slices.

[0179] Comparative Example 3

[0180] Preparation of DOPO-HQ and triazine-based flame-retardant PET composites:

[0181] By weight, 100 parts of PET chips, 10 parts of DOPO-HQ, and 5 parts of the intermediate product (triazine-based flame retardant) prepared in step 2 of Example 9 were added to a twin-screw extruder, and the temperature was set to: zone 1 temperature: 250°C; zone 2 temperature: 250°C; zone 3 temperature: 250°C; zone 4 temperature: 250°C; zone 5 temperature: 250°C to obtain a composite material of DOPO-HQ, triazine-based flame retardant and PET.

[0182] Performance Testing

[0183] The performance of the prepared PET composites was tested by vertical combustion test and limiting oxygen index method and compared with pure PET. The results showed that the prepared DOPO-HQ and triazine-based flame-retardant PET composites had droplet phenomenon during combustion, and the vertical combustion test was V-1 level. The peak smoke release rate and total smoke release were reduced by 13.2% and 7.0% respectively compared with PET slices.

[0184] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A DOPO-HQ-based flame retardant, characterized in that: Having the structure described in Formula 1: In formula I, 5≤n≤10; R includes 2. The method for preparing the DOPO-HQ-based flame retardant according to claim 1, characterized in that: The following steps are involved: In a protective atmosphere, cyanuric chloride, an aromatic compound, a first catalyst and a first organic solvent are mixed to perform a nucleophilic substitution reaction to obtain an intermediate product; The intermediate product, DOPO-HQ, a second catalyst and a second organic solvent are mixed to carry out a condensation reaction to obtain a DOPO-HQ-based flame retardant; The aromatic compound includes p-methylphenol, biphenyl alcohol, 3-phenylvinylphenol, 2-hydroxybenzimidazole or p-hydroxybenzonitrile.

3. The preparation method according to claim 2, characterized in that: The first catalyst comprises pyridine, triethylamine, sodium acetate or anhydrous potassium carbonate; the mass ratio of the cyanuric chloride, the aromatic compound and the first catalyst is 1-2.5:0.8-2.5:

1.

4. The preparation method according to claim 2 or 3, characterized in that: The first organic solvent includes ethanol, dichloromethane, chloroform or acetone; the temperature of the nucleophilic substitution reaction is 40-60° C., and the time is 2-4 hours.

5. The preparation method according to claim 2, characterized in that: The second catalyst includes pyridine, triethylamine, sodium acetate or N,N-diisopropylethylamine; the mass ratio of the intermediate product to DOPO-HQ is 1:1-1.8; the mass ratio of the intermediate product to the second catalyst is 1:0.5-1.

4.

6. The preparation method according to claim 2 or 5, characterized in that: The second organic solvent includes dimethyl sulfoxide, tetrahydrofuran, N,N-dimethylformamide or acetone; the temperature of the condensation reaction is 80-120° C., and the time is 10-12 hours.

7. Use of the DOPO-HQ-based flame retardant according to claim 1 or the DOPO-HQ-based flame retardant prepared by the preparation method according to any one of claims 2 to 6 in the preparation of flame-retardant and anti-drip PET composite materials.

8. A flame retardant and anti-drip PET composite material, characterized in that: The preparation method comprises the following raw materials in parts by weight: 100 parts of PET, 2 to 8 parts of DOPO-HQ-based flame retardant; The DOPO-HQ-based flame retardant is the DOPO-HQ-based flame retardant according to claim 1 or the DOPO-HQ-based flame retardant prepared by the preparation method according to any one of claims 2 to 6.

9. The method for preparing the flame-retardant and anti-drip PET composite material according to claim 8, characterized in that: The following steps are involved: PET and DOPO-HQ-based flame retardant are mixed and granulated in a twin-screw extruder to obtain a DOPO-HQ-based flame retardant PET composite material.

10. The preparation method according to claim 9, characterized in that: The temperature of the extruder is set as follows: zone 1 temperature: 255-265°C; zone 2 temperature: 255-265°C; zone 3 temperature: 265-275°C; zone 4 temperature: 265-275°C; zone 5 temperature: 265-275°C.

Citation Information

Patent Citations

  • Flame-retardant monomer containing DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) groups and preparation method and application of flame-retardant monomer

    CN103755742A

  • DOPO derivative flame retardant as well as preparation and application of DOPO derivative flame retardant

    CN105295300A

  • Hydrophobic DOPO derivative flame retardant and preparation method thereof

    CN106905370A

  • Novel DOPO-based flame retardant and preparation method thereof

    CN106928278A

  • DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) derivative fire retardant and preparation method and application thereof

    CN107739453A

Cited By

  • Triethylene glycol ammonium phosphate flame retardant, green flame-retardant finishing liquid and preparation method and application of triethylene glycol ammonium phosphate flame retardant and green flame-retardant finishing liquid

    CN119708047A

  • Flame-retardant modified PC-ABS plastic and preparation method thereof

    CN120737578A

  • Hydrazide-based phosphorus-nitrogen synergistic reaction type flame retardant as well as preparation method and application thereof

    CN121974950A

  • A hydrazide-based phosphorus-nitrogen synergistic reaction type flame retardant, a preparation method and application thereof

    CN121974950B